PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA BANK NAGARI - Afni Can; Yasri Yasri (Jurnal Riset Manajemen Bisnis dan Publik, 2016)
This study is intended to analyze the effects of work motivation, job satisfaction and organizational commitment to the performance of employees working in the Bank Nagari. The population in this study amounted to 1,449 employees and a sample of 313 respondents. Analysis of data using a proportional sample data. Data using questionnaires, observations and corporate data.Results of the study concluded that : 1) Motivation of significant and positive impact on job satisfaction at Bank Nagari, 2) Motivation give significant and positive impact on organizational commitment to the Bank Nagari, 3) job satisfaction affects insignificant and negative towards the organization's commitment to the Bank Nagari , 4) Working motivation give positive significant effect on employee performance Bank Nagari, 5) Job satisfaction does not give significant positive effect on employee performance through intervening Bank Nagari organizational commitment, 6) organizational commitment has a significant positive effect to employee performance Bank Nagari. Keywords: workmotivation, job satisfaction, organizational commitment, employeeperformance